Utilization of an eco-friendly bioactive yellow pigment from Streptomyces thinghirensis AF7 for making colored antimicrobial fabrics - Al-Tekreeti, Afnan R. A.; Luti, Khalid Jaber Kadhum (Iraqi Journal of Science, 2023)
Despite their long successful use, synthetic dyes have several problems due to their carcinogenic and toxic effects. Besides providing bright colors, some natural pigments have shown notable antimicrobial activity; thus, they could be utilized as functional dyes in many applications such as making colored antimicrobial textiles. In this work, a yellow pigment produced by Streptomyces thinghirensis AF7 and has a notable antimicrobial activity was used to produce a colored antimicrobial textile. The extracted yellow pigment was subjected to a purification step using silica gel column eluted with di ethyl ether solvent. The FTIR, GC-MS and NMR analysis showed that the colorings in this type of product are due to the presence of chromopeptides. The purified yellow pigment was effectively used to dye two types of fabrics (cotton and polyester). Results showed that polyester had more affinity for yellow pigment than cotton. The stability of dyed fabrics was verified based on ISO 105-E01:2013 which demonstrated that both dyed cotton and polyester fabrics had a considerable degree of fastness to water, seawater and detergent. Moreover, yellow dyed Polyester fabric exhibited more stability against acid than yellow dyed cotton fabric, and both were unstable against alkaline solution. Finally, the yellow dyed fabrics showed antibacterial properties against S. aureus proving that the antibacterial activities of the yellow pigment could be retained when the pigment is bound to the fabric.